Paleogene emergence and evolutionary history of the Amazonian fossorial fish genus Tarumania (Teleostei: Tarumaniidae) - Melo, Bruno F.; de Pinna, Mário C. C.; Rapp Py-Daniel, Lúcia H.; Zuanon, Jansen; Conde-Saldaña, Cristhian C.; Roxo, Fabio F.; Oliveira, Claudio (Frontiers in Ecology and Evolution, 2022)
Tarumania walkerae is a rare fossorial freshwater fish species from the lower Rio Negro, Central Amazonia, composing the monotypic and recently described family Tarumaniidae. The family has been proposed as the sister group of Erythrinidae by both morphological and molecular studies despite distinct arrangements of the superfamily Erythrinoidea within Characiformes. Recent phylogenomic studies and time-calibrated analyses of characoid fishes have not included specimens of Tarumania in their analyses. We obtained genomic data for T. walkerae and constructed a phylogeny based on 1795 nuclear loci with 488,434 characters of ultraconserved elements (UCEs) for 108 terminals including specimens of all 22 characiform families. The phylogeny confirms the placement of Tarumaniidae as sister to Erythrinidae but differs from the morphological hypothesis in the placement of the two latter families as sister to the clade with Hemiodontidae, Cynodontidae, Serrasalmidae, Parodontidae, Anostomidae, Prochilodontidae, Chilodontidae, and Curimatidae. The phylogeny calibrated with five characoid fossils indicates that Erythrinoidea diverged from their relatives during the Late Cretaceous circa 90 Ma (108–72 Ma), and that Tarumania diverged from the most recent common ancestor of Erythrinidae during the Paleogene circa 48 Ma (66–32 Ma). The occurrence of the erythrinoid-like †Tiupampichthys in the Late Cretaceous-Paleogene formations of the El Molino Basin of Bolivia supports our hypothesis for the emergence of the modern Erythrinidae and Tarumaniidae during the Paleogene.